Diagnóstico de vulnerabilidad sísmica en Cartago , Costa Rica. - Jiménez-Monge, Daniela (Instituto Tecnológico de Costa Rica, 2012)
In the province of Cartago had occurred several earthquakes which have destroyed and killed hundreds of people. Two of these histrical eartquakes occurred in the years 1910 and 1912; both were caused by local fault of Agua Caliente. Due to histrical and recent seismicity, it was chosen an area thas is located within the zone of inluence of that local fault, to permom a study of seismic risk and seismic vulnerabiliy diagnosis. The hazards maps were created by using the deterministic method; therefore, two seismic scenarios were dedined. The peak ground accelertaion was calculated by using the attenuation equations defined by Climent et. al (1994). For the first scenario, the peak ground accelerations were 1.5 m/s2 yand 3.5 m/s2, and for the second scenario between 2.5 m/s2 and 6.8 m/s2. Then, using a visual screening methodology , proposed by professionals of the National Emergency Commission, it was possible to obtain some imortant characteristics of the buildings inspected such as: age, general condition and type of structural system, that were divided into other characteristics or atributes, which have a level of vulnerability assiged, based of expert opinios. Finally, using the program ILWIS 3.3, was possble to relate all three attribute maps with the peak ground acceleration´s maps and estimate the damage in a qualitative way. For the first scenario, it is estimated that the 84,8% of the dwelling houses may suffer moderate to low damage, and 6,1% major damages, while, for the second scenario to 90,7% may suffer significant damage and the reamaining 9,3% major damages. Areas with major damage correspond to informal settlements, such as "slum".
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Aceleración máxima; Daño probable; Método determinístico; Amenaza sísmica; Falla agua caliente